PENGARUH KEPUASAN KERJA DAN IKLIM ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (STUDI PADA PERAWAT RSIA ERIA BUNDA PEKANBARU) - Saputra, Anggie Roy; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of job satisfaction and organizational climate on work oganizational citizenship behavior (ocb) nurses at RSIA Eria Bunda Pekanbaru. It was proposed two indenpendent variables and one dependent variable, namely job satisfaction and organizatinal climate as indenpendent variables and oganizational citizenship behavior (ocb) as a dependen variable.This research methods are descriptive and quantitative by using SPSS 21, where the sample used is nurses at RSIA Eria Bunda Pekanbaru with 71 respondents. To take the sample, the writer used cencus method. Technique of collecting data was through questionnarie and interview.  The result ofanalysis using the validity test, reability test, determination test, simple linear regression test, multiple linear regression test, t test, and f test. As the result, it can be seen that both the job satisfaction have significant on oganizational citizenship behavior (ocb), that organizational climate have significan effec on oganizational citizenship behavior (ocb). Job satisfaction and Organizational climate have a significan effec on oganizational citizenship behavior (ocb). Keywords: Job Satisfaction, Organizational Climate, and Oganizational                                 Citizenship Behavior.